Evaluation of Functional Mobility Outcomes Following Electrical Stimulation in Children With Spastic Cerebral Palsy. (June 2017) - Mukhopadhyay, Rupsha; Lenka, Prasanna K.; Biswas, Abhishek; Mahadevappa, Manjunatha
This study investigated the clinical feasibility of electrical stimulation in enhancing ankle dorsiflexion of the tibialis anterior muscle to improve mobility in children with spastic cerebral palsy. The intervention group received electrical stimulation therapy for 30 minutes and physiotherapy for another 30 minutes for 5 days a week, up to 12 weeks. Gait parameters, Gross Motor Function Measure, Physiological Cost Index, surface electromyogram, and electroencephalogram (EEG) data were recorded pre- and posttreatment. Data were compared with the control group, which received only conventional physiotherapy for 60 minutes. There was an increase in walking speed (17.67%) and Gross Motor Function Measure scores (2.1%) while the Physiological Cost Index value was decreased (19.7%). The analysis of features extracted from the surface electromyogram showed an increase in muscle strength and that of EEG showed increased motor activities. Hence, electrical stimulation combined with conventional physiotherapy improve gait, muscle strength, and motor activities in children with spastic cerebral palsy.